Development of a geospatial-based environmental vulnerability index for watersheds as it affects climate change in the Philippines - Tiburan, Cristino L., Jr.; Saizen, Izuru; Mizuno, Kei; Kobayashi, Shintaro (2010)
Over the past decades, the term vulnerability has been extensively defined and studied in various researches. While there are dissimilarities on how it is utilized, its scope and application have been found to be of great importance in understanding the dynamics of several phenomena. It has been widely applied in several fields of interest such as natural hazards, food security, human health, and recently, to climate change studies. This study is particularly focused on developing an approach that integrates geospatial-based technology in vulnerability assessment of watersheds to climate change in the Philippines. The model involves 21 indicators that are classified under three major components, namely exposure, sensitivity, and adaptive capacity component. Each indicator is given a scale of 1 to 5 to signify the degree of vulnerability. The threshold levels for each scale are determined based on statistical test and use of existing geospatial-based techniques. An overall vulnerability point is also generated to indicate the general assessment of the landscape. Moreover, the sub-indices in the model provide an avenue to evaluate the extent of damage brought about by other pertinent issues associated with climate change such as flood, drought, erosion and landslide, and biodiversity loss. All these information will play a significant role in the effective and efficient management of watersheds in the country as well as in targeting policy interventions associated with climate change.
Keywords: Climate change; Watershed management